Technology Acceptance and Self-Directed Learning: Mediation Role of Positive Emotions, Learning Motivation and Technological Self-Efficacy - Aabeyir, Boniface; Aabeyir, Raymond; Amoako, Samuel; Ohene Boateng, Francis (International Journal of Mathematics and Mathematics Education (IJMME), 2025)
This study investigated the relationship between technology acceptance and self-directed learning among students in the colleges of education in the Ashanti region of Ghana, with a focus on the mediating roles of positive emotions, learning motivation, and technological self-efficacy. With a sample of 237 students and employing Smart Partial Least Squares Structural Equation Modelling, the study revealed that technology acceptance positively influenced technological self-efficacy, learning motivation and positive emotions. The study also indicated that technological self-efficacy and learning motivation insignificantly predicted students’ self-directed learning, while positive emotions significantly predicted students’ self-directed learning. The analysis identified learning motivation and technological self-efficacy as insignificant mediators in this relationship, but positive emotions positively and significantly mediated the relationship. It is recommended that the Colleges of Education in Ghana should focus on increasing student's confidence in their technological abilities through targeted training programmes and support resources.